The Impact of Perfect Image Portrayal on TikTok (Douyin) on Appearance Anxiety Among Young Chinese Women - Li Dianze (SHS Web of Conferences)
Social media, especially visual platforms such as Douyin, have greatly influenced the values of young Chinese people, especially young women. The prevalence of idealised body images and aesthetic standards on social media has contributed to physical anxiety and hurt self-cognition and mental health. The purpose of this study is to explore how the perfect image shaping on Douyin affects the appearance anxiety of young Chinese women, their mental health and self-perception. Analysing social media usage patterns highlights the significant trend of young women. Many respondents use social media for more than 30 minutes a day, especially on TikTok. These users often encounter idealised images. Despite widespread suspicion, more than half of them think that these images are real to some extent. This exposure leads to anxiety about appearance, and more than 25% of young women suffer from moderate anxiety. This anxiety has fuelled people’s desire for beauty or plastic surgery, and 62.5% of people try to achieve their ideal appearance through self-care and exercise. Popular beauty filters and image enhancement tools on social media further exacerbate this anxiety because they promote unrealistic beauty standards.